One-step synthesis of carbon nitride nanobelts for the enhanced photocatalytic degradation of organic pollutants through peroxydisulfate activation. Issue 1 (18th December 2020) - Zheng, Xiaoshan; Wang, Zhongquan; Chen, Tiansheng; Ran, Jie; Wu, Yuliang; Tan, Cuiwen; Zhang, Qianxin; Chen, Ping; Wang, Fengliang; Liu, Haijin; Lv, Wenying; Liu, Guoguang
Abstract : Photocatalytic mechanism of sulfamethazine degradation under a CNNB/PDS/blue-LED system, in which the enhanced photocatalytic activity might be ascribed to an external dual transmission mechanism. Abstract : The progress of high-efficiency photocatalysts and the suppression of photoinduced charge recombination remain the primary goals for practical applications. In this study, we demonstrate the convenient synthesis of graphite carbon nitride nanobelts (CNNB) for the enhanced photocatalytic degradation of organic contaminants through peroxydisulfate (PDS) activation. In operation, the PDS serves as an electron acceptor, whereas the organic pollutants acts as hole catchers, thus achieving an external dual transmission mechanism. Consequently, the CNNB/PDS system shows outstanding photocatalytic performance for the removal of sulfamethazine (SMT) under blue-LED light irradiation, which was ∼17- and ∼5 times more efficient than pristine g-C3 N4 /PDS and CNNB, respectively. Furthermore, a potential SMT degradation pathway was deduced based on the detection of degradation intermediates and theoretical calculations. Finally, reactions looking at several influencing factors indicated that the CNNB/PDS system could be used far more productively for the removal of SMT under ambient aqueous conditions. Hence, this synergistic external dual transmission mechanism process might serve as a promising technology for the removal of organic pollutants.